Factors Influencing Household Electronic Waste (E-Waste) Recycling Participation - Nazatul Faizah, Haron; Shaufique F., Sidique; Alias, Radam (2018)
The amount of electronic waste (e-waste) has relatively increased along with the rapid increases in technological and economic development in Malaysia. In order to avoid dumping massive amounts of electronic waste in landfills, recycling programs were implemented by policymakers and governments to attract people to participate in these programs. The success of recycling programs largely depends on household participation and their commitment. Therefore, a better understanding on recycling behaviour will help to design and improve the effectiveness of these programs. This paper studies the profile of people who are involved in recycling activities and examines the factors influencing household recycling participation. The findings of this study suggests that socioeconomic variables, for example, education and income, are the predictors of recycling behaviour. Attitudinal factors were also found to affect recycling participation, such as ATTITUDE, BELIEF, CONVENIENCE, KNOWLEDGE, and SOCIAL PRESSURE